(untitled) (Research, Society and Development, 2022)
Gastroesophageal reflux disease (GERD) is a common clinical problem that affects millions of people worldwide. Advances in the therapeutic modality of the disease are essential to achieve the effectiveness of different imposed conditions, such as treatment refractoriness. The present review study sought to assess new evidence for the treatment of GERD, documented through clinical and randomized studies. This is an integrative review research carried out through an advanced search in the PubMed database, which took into account the following inclusion criteria: clinical trials and controlled and randomized trials; articles published in the last year; that had a full text available, in Portuguese, English or Spanish and that addressed the treatment of GERD. Duplicate articles in the database and those that did not address the topic under study were excluded. It was found that surgical techniques such as endoscopic surgery for PPI-refractory GERD and endoscopic fundoplication obtained good results in the analyzed context, in addition to techniques such as modified Xiaochaihu decoction and the use of JianpiQinghua granules in Traditional Chinese Medicine, in addition to the use of herbal species such as Opuntia ficus-indica and Olea europaea, which could demonstrate significant improvement in the main symptoms of GERD.